Research on the flow characteristics of blasthole stemming slurry in open-pit mining - Li, Pingfeng; Xie, Shoudong; Lu, Junji; Li, Mengyuan; Peng, Xiaopeng; Yang, Kai; Zhang, Lei (Frontiers in Earth Science, 2024)
The flow characteristics of blasthole stemming slurry (BSS), predominantly comprising yellow mud (YM), tail mud (TM), or drilling cuttings (DC), were systematically investigated. Various influencing factors, including slurry mass concentration, the addition of TM or DC, and the mass ratio of TM to YM (TM/YM) and DC to YM (DC/YM), were meticulously examined. Experiments were conducted to assess the fluidity, rheological properties, and bleeding rate of BSS samples, which were prepared by manipulating slurry mass concentration and the proportions of TM or DC. The results indicate that the rheological properties of BSS are suitably described by the Herschel-Bulkley model. A critical mass concentration was identified, beyond which the flowability of BSS rapidly deteriorates.Replacing YM with an equivalent amount of TM at a mass concentration of 59% increased the yield stress by 167.30%, while reducing the bleeding rate to 0 within the 53% to 59% mass concentration range.Conversely, replacing YM with DC at a mass concentration of 62% reduced the yield stress by 63.96%, while increasing the 60-minute bleeding rate from 0 to 1.44%. Increasing the TM/YM ratio resulted in reduced fluidity, elevated yield stress, and a variable degree of shear thickening. The degree of shear thickening was highest when the TM/YM ratio was 1, with significant impacts on differential viscosity at higher shear rates. On the other hand, increasing the DC/YM ratio enhanced fluidity, decreased yield stress, and influenced the degree of shear thickening and differential viscosity, with the highest shear thickening and lowest differential viscosity observed at a DC/YM ratio of 3. The bleeding rate of BSS consistently rose with the increase in the DC/YM ratio.